Evaluación del control químico de la Antracnosis (Colletotrichum lindenuthianum) en el cultivo de fréjol (Phaseolus vulgaris L.) variedad – Toa en la zona de Cahuasquí Provincia de Imbabura - Unigarro Salazar, Milton Jefferson (2013)
The present study was aimed to evaluate the effectiveness and efficiency of six commercial use fungicides to control anthracnose in growing fickle or climbing bean (Phaseolus vulgaris L.) variety "Toa" caused by (Colletotrichum lindemuthianum), under natural conditions in Cahuasquí - Imbabura, located at 78 ° 12'40 "W, 00 ° 31'05" N, at an altitude of 2335 meters. The experimental design was RCBD (Design of randomized complete blocks) with six treatments and four replications with a one witness, and a total of 28 experimental units of 12 m2, with a total area of 609 m2 and a distance between treatments and blocks 1 m.